(untitled) (Muitas Vozes, 2024)
This article aims to analyze the extent to which traits of poetic language are compatible and incompatible with the musical language in the transposition of the poem to the song “poema da mulher suja” (2022), which has, as lyrics, the poem by Angélica Freitas of the same title, appropriated by Vitor Ramil, who, from this, produces the arrangement of the song with double authorship. In this sense, the investigation of compatibilities and incompatibilities in “poema da mulher suja”, by traversing the concepts of figurativization, passionalization and thematization suggested by Luiz Tatit in A canção: eficácia e encanto (1986), it exposes new associations between the linguistic and musical components, putting into question the notion of effectiveness of the song and, thus, the integral preservation of the aesthetic paradigm.